A one-pot solid-state synthesis of MgO nanoparticles and their catalytic, biological, and electrochemical sensor activities: hexaaquamagnesium(ii) bis(6-oxo-1, 6-dihydropyridine-3-carboxylate) as a tool. (30th January 2023) - Balakrishnan, Prabha Devi; Arunadevi, Natarajan; Rath, Nigam P.; Kanchana, Ponnusamy; Premkumar, Thathan
Abstract : MgO nanoparticles produced from a solid-state precursor, hexaaquamagnesium(ii ) bis(6-oxo-1, 6-dihydropyridine-3-carboxylate), showed proficient catalytic activity and enhanced biological and electrochemical sensor activities. Abstract : A new divalent Mg complex, hexaaquamagnesium(ii ) bis(6-oxo-1, 6-dihydropyridine-3-carboxylate) ([Mg(H2 O)6 ](C6 H4 NO3 )2 ) (1 ), was synthesized by reacting Mg(NO3 )2 ·6H2 O with 6-hydroxypyridine-3-carboxylic acid (6-hpca) in the presence of aminoguanidine bicarbonate. Here, 1 was studied by elemental, infrared (IR), 1 H NMR, 13 C NMR, ultraviolet-visible (UV-vis), thermal, and single-crystal X-ray diffraction (SC-XRD) analyses. We discovered that 1 crystallized in the triclinic P 1̄ space group, whereas the Mg(ii ) ion exhibited six coordinated water molecules with octahedral geometry. Interestingly, 1 was used as a solid-state precursor for synthesizing Mg oxide (MgO) nanoparticles (NPs). Fourier transform infrared (FT-IR), UV-vis, powder-XRD, TEM, and energy-dispersive X-ray spectroscopic analyses were performed on the prepared MgO NPs. The results showed that the as-prepared MgO NPs were small (14 nm) and homogeneous. The antibacterial activity and antioxidant scavenging assays of 6-hpca, 1, and the MgO NPs against 2, 2-diphenyl-1-picrylhydrazyl (DPPH) revealed that the MgO NPs had good biological properties. Furthermore, a sensitive electrochemical sensor was developed for improved glucose detection by modifying a glassy carbon electrode with the as-prepared MgO NPs. The MgO NPs demonstrated effective catalytic properties for the reduction of 4-nitrophenol to 4-aminophenol. The proposed approach is simple, environmentally friendly, and user-friendly.